2022
DOI: 10.2147/jhl.s345528
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Commitment and Organizational Justice Among Health Care Workers in Ethiopian Jimma Zone Public Health Facilities

Abstract: Background The healthcare service sector is confronting a global labor shortage. Despite this fact, health care professionals are still highly vulnerable to organizational injustice, which negatively influence organizational commitment, putting an additional burden on the health sector. Thus, this study aimed to investigate the correlation between organizational commitment and organizational justice among health care workers. Methods Facility-based cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This implying that the health workers who have a high perception of procedural justice have a higher chance to provide better clinical decision-making outcome. This stud is in line with Deressa et al (2022) who reported that health workers who have a string perception of organizational justice tend to show more commitment to work than their counterparts who have low perception of procedural justice. These authors suggest that organizational justice has been acknowledged as a stimulus factor influencing healthcare workers level of organizational commitment leading to better decision-making outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…This implying that the health workers who have a high perception of procedural justice have a higher chance to provide better clinical decision-making outcome. This stud is in line with Deressa et al (2022) who reported that health workers who have a string perception of organizational justice tend to show more commitment to work than their counterparts who have low perception of procedural justice. These authors suggest that organizational justice has been acknowledged as a stimulus factor influencing healthcare workers level of organizational commitment leading to better decision-making outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…For interpretation, Beta and Adjusted R2 were used, and statistically significant predictors were declared at a p-value of 0.05 and a 95% confidence interval. 31 …”
Section: Methodsmentioning
confidence: 99%
“…Then the schools' management, or the authorities, should employ good strategies to maintain procedural justice to maintain the principals' affection for their job. Designing intervention (Primawidi & Mangundjaya, 2020) as a part of persevering such a commitment (Deressa et al, 2022) is decisive to make.…”
Section: Organizational Justice Direct Effect On Affective Commitmentmentioning
confidence: 99%